2013
DOI: 10.1177/0971685812470345
|View full text |Cite
|
Sign up to set email alerts
|

Paradigms of Quality of Work Life

Abstract: Quality of work life (QWL) is generally associated with a series of objective organizational conditions and practices that enables employees of an organization to perceive that they are virtually safe, satisfied and have better chances of growth and development as individual human beings. QWL is nowadays drawing more attention globally as in modern society people spend about more than one-third of their lives at their workplace. Hence, the eminence and importance of QWL is unparalleled and unquestionable. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 11 publications
0
33
0
9
Order By: Relevance
“…There is relatively widespread agreement that "quality of work" represents "a multifaceted paradigm, built upon a number of interrelated factors that seek meticulous consideration to conceptualize and measure" [41,42]. The International Labour Organization (ILO) uses the term "decent work", which it defines in terms of "opportunities for women and men to obtain decent and productive work, in conditions of freedom, equity, security and human dignity" [10,11].…”
Section: Sustainability and Quality Of Working Lifementioning
confidence: 99%
“…There is relatively widespread agreement that "quality of work" represents "a multifaceted paradigm, built upon a number of interrelated factors that seek meticulous consideration to conceptualize and measure" [41,42]. The International Labour Organization (ILO) uses the term "decent work", which it defines in terms of "opportunities for women and men to obtain decent and productive work, in conditions of freedom, equity, security and human dignity" [10,11].…”
Section: Sustainability and Quality Of Working Lifementioning
confidence: 99%
“…Bardick, Bernes, Magnusson & Witko (2005) menjelaskan bahwa perencanaan karier sangat penting untuk siswa. Selanjutnya, Ahmad (2013) menjelaskan bahwa perencanaan karier sudah dimulai semenjak seseorang berada pada bangku sekolah. Berdasarkan pendapat tersebut maka dapat disimpulkan, bahwa perencanaan karier pada siswa merupakan hal yang penting dibangun untuk menumbuhkan sikap siswa dalam menempuh karier masa depan.…”
Section: Pendahuluanunclassified
“…Importantly, quality of work life should not be perceived as a complex venture that stems the inventions and technological advancement, because it is emerges from day-to-day activities in the workplace channeled towards organization's survival and prosperity S. Ahmad (2013). Therefore, the chief concern for many organizations is their policy how to organize and stimulate it to balance employee and organizational demands.…”
Section: Organizational Policymentioning
confidence: 99%
“…However, it is imperative for management to understand the value of employee contribution to organizational policy because it help management and employee to agree on common goal towards achieving organizational vision, Consequently, the creative ideal of employee is required to champion organizational performance. S. Ahmad (2013) suggested that a better understanding of the interrelationship of various aspects of quality of work life (QWL) provides an opportunity for improved analysis of cause and effect in the workplace. (S. Ahmad, 2013) stated that employees believe that they have a high QWL when there is a clear sense of openness and trust between management and employees and no fear of being short-changed or misguided in task performance in discharging their action.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation